Plasma Cells, the Next Generation: Beyond Antibody Secretion - Pioli, Peter D. (Frontiers in Immunology, 2019)
Plasma cells (PCs) represent the terminal differentiation step of mature B lymphocytes. These cells are most recognizable for their extended lifespan as well as their ability to secrete large amounts of antibodies (Abs) thus positioning this cell type as a key component of humoral immunity. However, it is now appreciated that PCs can have far reaching effects on pathologic as well as non-pathologic processes independent of Ab secretion. This is highlighted by recent studies showing that PCs function as key regulators of processes such as hematopoiesis as well as neuro-inflammation. In part, PCs accomplish this by integrating extrinsic signals from their environment which dictate their downstream functionality. Here we summarize the current understanding of PC biology focusing on their ever-growing functional repertoire independent of Ab production. Furthermore, we discuss potential applications of PC immunotherapy and its implementation for translational benefit.